Environmentally realistic concentrations of cocaine in seawater disturbed neuroendrocrine parameters and energy status in the marine mussel Perna perna - Fontes, Mayana Karoline [UNESP]; Dourado, Priscila Leocadio Rosa [UNESP]; Campos, Bruno Galvão de [UNESP]; Maranho, Luciane Alves [UNESP]; Almeida, Eduardo Alves de; Abessa, Denis Moledo de Souza [UNESP]; Pereira, Camilo Dias Seabra (Elsevier, 2022)
Cocaine (COC) is a powerful illicit drug frequently detected in the aquatic environment. COC acts by inhibiting the reuptake of dopamine (DOPA) and 5-hydroxytryptamine (5-HT – serotonin) and causes endocrine disturbances in mammals. This study investigated similar effects from cocaine exposure in the marine mussel Perna perna, as well as neurotoxicity and energy imbalances. Mussels were exposed to COC (0.2 μg.L−1 and 2 μg.L−1) for periods of 48, 96, and 168 h. Acetylcholinesterase (AChE) was measured in adductor muscle tissue to determine neurotoxicity, and neurotransmitter levels (DOPA and 5-HT), monoamine oxidase (MAO) and cyclooxygenase (COX) activity, and energy status (mitrochondrial electron transport, MET, and total lipids, TLP) were evaluated in the mussels' gonads. COC decreased AChE activity in the mussels exposed to 0.2 μg.L−1 and 2 μg.L -1 after 168 h, and all concentrations of COC increased neurotransmitter levels. Increases in MET (0.2 μg.L -1, for all exposure periods) and TLP (0.2 μg.L 1 after 48 h, and 2 μg.L -1 after 96 h and 168 h) were also observed. No significant change was detected in MAO activity. COC also decreased COX activity in the mussels exposed to 0.2 μg.L -1 (48 h and 96 h) and 2 μg.L -1 (96 h). These results suggest that COC may compromise neurotransmitter levels and COX activity. Furthermore, the changes in MET and LPT suggest that COC affects the energy balance of the mussels, and could negatively affect physiological processes such as metabolism, hormone production, and embryonic development.
Keywords: Bivalves; Energy balance; Illicit drugs; Marine pollution; Neurotoxicity